2021
DOI: 10.1016/j.msea.2020.140449
|View full text |Cite
|
Sign up to set email alerts
|

Deformation induced twinning in hcp/bcc Al10Hf25Nb5Sc10Ti25Zr25 high entropy alloy – microstructure and mechanical properties

Abstract: High-entropy alloys of hexagonal structure commonly revealing high strength but very limited ductility, still remain a challenging task. Advanced strategy is proposed in present work in order to develop high-entropy alloy of chemical composition Al 10 Hf 25 Nb 5 Sc 10 Ti 25 Zr 25 at.%. Crystallographic features and microstructures of as-cast and annealed Al 10 Hf 25 Nb 5 Sc 10 Ti 25 Zr 25 at.% alloy are characterized by X-ray diffraction, scanning and highresolution transmission electron microscopies, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 64 publications
0
0
0
Order By: Relevance
“…Attempts to ductilize refractory BCC high entropy alloys have been conducted on refractory elements based four or five multi-components high entropy alloys through metastability engineering, from which the deformation mechanisms of BCC high entropy alloys can be tailored from dislocation slip to transformation induced plasticity (TRIP) by tuning the parent BCC phase stability [5,6]. The strengthening effects of martensitic phase transformation have been extensively studied and found that with varying BCC phase stabilities, stress/strain-induced hexagonal α [5][6][7], hexagonal α' [8][9][10] and orthorhombic α'' [11][12][13] phase transformation could be successfully activated in refractory BCC high entropy alloys. The resultant TRIP effects effectively alleviated the plastic instability in refractory BCC high entropy alloys, thus improving the uniform ductility by maintaining an appreciable work-hardening capability.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to ductilize refractory BCC high entropy alloys have been conducted on refractory elements based four or five multi-components high entropy alloys through metastability engineering, from which the deformation mechanisms of BCC high entropy alloys can be tailored from dislocation slip to transformation induced plasticity (TRIP) by tuning the parent BCC phase stability [5,6]. The strengthening effects of martensitic phase transformation have been extensively studied and found that with varying BCC phase stabilities, stress/strain-induced hexagonal α [5][6][7], hexagonal α' [8][9][10] and orthorhombic α'' [11][12][13] phase transformation could be successfully activated in refractory BCC high entropy alloys. The resultant TRIP effects effectively alleviated the plastic instability in refractory BCC high entropy alloys, thus improving the uniform ductility by maintaining an appreciable work-hardening capability.…”
Section: Introductionmentioning
confidence: 99%